1890
DOI: 10.1002/jmor.1050040203
|View full text |Cite
|
Sign up to set email alerts
|

On the gustatory organs of some of the mammalia

Abstract: INDEX OF SPECIES .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1927
1927
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…According to Stadtmuller ('38), the tongue of Myomorpha belongs to the first type, Leoporidae, Hystricidae, Erethizontidae and Spalacidae to the second and Sciuridae, Castoridae, Lagomyidae, Nesomyidae, Dipodidae, Cricetomys and Ctenodactylus to the third. It has been accepted that the triangular arrangement of three vallate papillae in the third type is the most primitive pattern of the mammalian tongue (Honigschmied, 1872;Tuckerman, 1891;Munch, 1896;Oppel, '00;Sonntag, '24-'25;Stadtmuller, '38). Hence, it can be said that among Lagomorpha the pika's tongue with three vallate papillae is more primitive than that of Lepus having two papillae.…”
Section: Discussionmentioning
confidence: 99%
“…According to Stadtmuller ('38), the tongue of Myomorpha belongs to the first type, Leoporidae, Hystricidae, Erethizontidae and Spalacidae to the second and Sciuridae, Castoridae, Lagomyidae, Nesomyidae, Dipodidae, Cricetomys and Ctenodactylus to the third. It has been accepted that the triangular arrangement of three vallate papillae in the third type is the most primitive pattern of the mammalian tongue (Honigschmied, 1872;Tuckerman, 1891;Munch, 1896;Oppel, '00;Sonntag, '24-'25;Stadtmuller, '38). Hence, it can be said that among Lagomorpha the pika's tongue with three vallate papillae is more primitive than that of Lepus having two papillae.…”
Section: Discussionmentioning
confidence: 99%
“…From descriptions of previous workers (Martin, 1836;Owen, 1836Owen, , 1852Mayer, 1844;Flower, 1872;Honigschmied, 1873;Young, 1881;Poulton, 1833a, b;Tuckerman, 1889aTuckerman, , b, 1890Tuckerman, , 1891Tuckerman, , 1892Munch, 1896;Parsons, 1896;Windle and Parsons, 1898;Oppel, '00;Sonntag, '24, '25;Stadtmuller, '38), it is obvious that the tongue of marsupials has three circumvallate papillae arranged in an inverted V-shape. However, there are some differences between their structures; the anterior papilla is much larger than the posterior.…”
Section: Discussionmentioning
confidence: 99%
“…The tongue of the marsupials has been extensively investigated (Martin, 1836;Owen, 1836Owen, , 1852Mayer, 1844;Flower, 1872;Honigschmied, 1873;Young, 1881;Poulton, 1883a, b;Tuckerman, 1889aTuckerman, , b, 1890Tuckerman, , 1891Tuckerman, , 1892Munch, 1896;Parsons, 1896;Windle and Parsons, 1898;Oppel, '00;Sonntag, '24, '25;Stadtmuller, '38). The data reported by these investigators may be summarized as follows: ( 1 ) Three circumvallate papillae are arranged i n an inverted V-shape.…”
mentioning
confidence: 99%
“…Rabbit tongues have been useful for morphological studies. The majority of studies, however, have been restricted to epithelial cells or to the gustatory epithelium, particularly the taste buds of well-developed foliate papillae (Tuckerman, 1890; Omar Trujillo-Cenoz, 1957; Scalzi, 1967;Toyoshima and Shimamura, 1981;Liu and Lee, 1982;Iwasaki, 1987;Kobayashi, 1992). Stereo structure of both the lingual papillae and their CTC of rabbits is provided by Silva et al (2002), but more detailed study has been demonstrated herein.…”
Section: Introductionmentioning
confidence: 90%